2016
DOI: 10.5965/223811711522016124
|View full text |Cite
|
Sign up to set email alerts
|

Altura de manejo da pastagem, época de dessecação de Urochloa ruziziensis e adubação nitrogenada na cultura da soja em sistema integração lavoura-pecuária

Abstract: Altura de manejo da pastagem, época de dessecação de Urochloa ruziziensis e adubação nitrogenada na cultura da soja em sistema integração lavoura-pecuária PALAVRAS-CHAVE:crescimento da soja, acúmulo de N, componentes de rendimento, Glycine max. ABSTRACTThe integration of soybean crop with pastures is an important strategy to diversify the grain production systems in Brazil. The objective of this research was to evaluate the effect of grazing intensities in Urochloa ruziziensis, desiccation time of the pasture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
(17 reference statements)
1
5
0
1
Order By: Relevance
“…However, under late desiccation the values of LAI at R2 stage (>5.2) were enough to reach high grain yields (Tagliapietra et al, 2018). Under similar conditions to this study, Balbinot et al (2016a) observed that earlier desiccation of U. ruziziensis pasture intensified soybean growth at the early developmental stages, but did not influence soybean biomass, shoot N concentration, and N accumulation at 60 days after emergence. Evaluating desiccation intervals of U. ruziziensis between 8 and 35 days before soybean sowing, Franchini et al (2015a) observed greater soybean biomass accumulation at 12 and 30 days after emergence with larger intervals between desiccation and soybean sowing, indicating better conditions for initial plant growth.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…However, under late desiccation the values of LAI at R2 stage (>5.2) were enough to reach high grain yields (Tagliapietra et al, 2018). Under similar conditions to this study, Balbinot et al (2016a) observed that earlier desiccation of U. ruziziensis pasture intensified soybean growth at the early developmental stages, but did not influence soybean biomass, shoot N concentration, and N accumulation at 60 days after emergence. Evaluating desiccation intervals of U. ruziziensis between 8 and 35 days before soybean sowing, Franchini et al (2015a) observed greater soybean biomass accumulation at 12 and 30 days after emergence with larger intervals between desiccation and soybean sowing, indicating better conditions for initial plant growth.…”
Section: Resultssupporting
confidence: 75%
“…In addition, if pasture is desiccated less than 10 days before soybean sowing, it may be difficult to cut the straw, and, consequently, the contact of the seeds with the soil is impaired by the residues (Ricce et al, 2011;Franchini et al, 2014). Early desiccation was more adequate for deposition of seeds and fertilizer, favoring plant emergence, as also confirmed by Balbinot et al (2016a).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A Braquiária é uma espécie forrageira bastante utilizada pelos produtores de grãos no sistema-integração-lavoura-pecuária, entretanto são poucas as informações sobre o manejo desta espécie sobre intensidade de pastejo e efeitos na cultura da soja em sucessão (Ferreira et al, 2015;Franchini et al, 2015aFranchini et al, , 2015bBalbinot Junior et al, 2016).…”
Section: Introductionunclassified
“…With a greater extraction of nutrients, its growth can be beneficed, but, with competition each other, it is limiting factor to accumulation of mass in its aerial part or root. Nowadays, Urochloa grasses are widely used aiming dry mass to no-till farming of soybean culture, as reported by Balbinot et al (2016). It is remarkable that is necessary an efficient desiccation to avoid the presence of grasses competing with the soybean culture.…”
Section: Resultsmentioning
confidence: 99%